Reusable Copper Catechol‐based Porous Polymers for the Highly Efficient Heterogeneous Catalytic Oxidation of Secondary Alcohols. Issue 19 (7th September 2022) - Henrion, Mickaël; Mohr, Yorck; Janssens, Kwinten; Smolders, Simon; Bugaev, Aram L.; Usoltsev, Oleg A.; Quadrelli, Elsje Alessandra; Wisser, Florian M.; De Vos, Dirk E.; Canivet, Jérôme
Abstract: New catechol‐based porous polymers were synthesized and used as platforms for the heterogenization of molecular Cu complexes. The resulting Cu@CatMP‐1 materials proved to be highly stable and performing catalysts for the oxidation of secondary alcohols with turnover numbers up to 6000, about 1 to 2 orders of magnitude higher than the current relevant state of the art, using catalyst loadings as low as 25 ppm of Cu. The solid catalyst proved to be recyclable for over 10 runs without detectable metal leaching and has been scaled to the gram scale. The coordination of Cu to catechol within the polymer has been evidenced by X‐ray absorption spectroscopy. Abstract : Porous polymer supports : Catechol‐based porous polymers (CatMP‐1) were demonstrated as platforms for the heterogenization of Cu complexes. Cu@CatMP‐1 proved to be highly stable and performing heterogeneous catalysts for the selective oxidation of secondary alcohols with turnover numbers up to 6000 and catalyst loadings as low as 25 ppm of Cu. The catalyst can be recycled for over 10 runs with stable catalytic activity.